The Impact of Dormitory Program on Students’ Biology Learning Activity and Autonomy - Wenny Pinta Litna Tarigan; Herbert Sipahutar; Fauziyah Harahap; Heru Kuswanto; Christine Ulina Tarigan (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
This study examines the differences in learning activity and autonomy between Grade 11 students in the boarding and non-boarding programs at SMAN 2 Balige. Total sampling was conducted from a population of 180 students; 90 students were in the boarding program, while the remaining 90 were in the non-boarding program. Data was gathered through two questionnaires focusing on learning activity and autonomy. The findings also showed that boarding students demonstrated higher learning autonomy than their non-boarding peers, as proved by the positive and significant value of an independent paired t-test. These results carry important policy implications for leveraging the benefits of dormitory programs to enhance educational oversight and performance.